Human regulatory T cells suppress proliferation of B lymphoma cells. Issue 8 (2nd August 2016) - Grygorowicz, Monika Anna; Biernacka, Marzena; Bujko, Mateusz; Nowak, Eliza; Rymkiewicz, Grzegorz; Paszkiewicz-Kozik, Ewa; Borycka, Ilona Sara; Bystydzienski, Zbigniew; Walewski, Jan; Markowicz, Sergiusz
Abstract: Activated regulatory T cells (Tregs) suppress proliferation and differentiation of normal B cells. In our study, allogeneic polyclonal CD4 + CD25 + Tregs and CD4 + CD25 + CD127 lo Tregs expanded in vitro in the presence of rapamycin and low dose IL-2 suppressed proliferation of 11 out of 12 established lymphoma B-cell lines. The effect of expanded CD4 + CD25 + Tregs on survival of freshly isolated lymphoma B cells maintained in culture with soluble multimeric CD40L and IL-4 was variable across lymphoma entities. The survival of freshly isolated follicular lymphoma cells usually decreased in cocultures with CD4 + CD25 + Tregs. Treg effect on chronic lymphocytic leukemia/small lymphocytic lymphoma cells ranged from suppression to help in individual patients. CD4 + CD25 + Tregs or CD4 + CD25 + CD127 lo Tregs expanded ex vivo with rapamycin could be used to suppress regrowth of residual lymphoma after autologous hematopoietic cell transplantation (HCT), and to counteract both graft-versus-host disease and lymphoma re-growth after allogeneic HCT in select patients with lymphoma susceptible to the regulation by Tregs.